Correlation between prefrontal-striatal pathway impairment and cognitive impairment in patients with leukoaraiosis. Issue 17 (April 2017) - Wang, Shuangkun; Yuan, Junliang; Guo, Xiaojuan; Teng, Leilei; Jiang, Hua; Gu, Hua; Hu, Wenli; Jiang, Tao
Abstract : Abstract: Our study aimed to investigate the changes of white matter microstructure of cortico-subcortical pathways using diffusion tensor imaging (DTI), and to explore the relationship between abnormal parameters of DTI and cognitive function underlying in patients with leukoaraiosis (LA). A total of 42 patients with LA and 42 age- and sex-matched healthy controls were recruited from Beijing Chaoyang Hospital, Capital Medical University between January 2012 and December 2012. All the subjects underwent scans of conventional magnetic resonance imaging and DTI, and a comprehensive neuropsychological battery was utilized. The regions of interest (ROIs) were located at the white matter of centrum semiovale, anterior and posterior periventricular white matter, basal ganglia, corpus callosum. The averaged values of mean diffusivity (MD) and fractional anisotropy (FA) were quantified both within white matter lesions (WMLs) and normal appearing white matter (NAWM). A linear regression analysis was performed to assess the association between diffusion parameters and decline in cognitive domains. Patients with LA were associated with comprehensive cognitive function deficits. We found that significantly decreased FA and increased MD in WMLs at the 5 ROIs than that of NAWM and controls ( P < .05). The values of FA in NAWM were significantly lower and MD in NAWM were significantly higher at centrum semiovale and posterior periventricular white matter than that of controls ( P < .05). The values of FA in WMLs at anterior periventricular white matter were positively related to the performances of cognition in patients with LA ( P < .05). The values of FA in NAWM located at anterior periventricular white matter were positively related to the score of Digit-symbol test ( r = 0.446, P = .002). The values of FA in NAWM located at anterior periventricular white matter correlated inversely with the Z scores of executive function ( r = −0.418, P = .03). In our study, patients with LA exhibited significant cognitive impairment especially in the domains of executive function. The technique of DTI revealed that the reduced FA and increased MD at the corresponding regions of cortico-subcortical pathways in patients with LA. DTI may be of great help for an early pathology of white matter microstructure underlying in patients with LA.